2010
DOI: 10.1007/s10951-009-0160-6
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing total tardiness in a stochastic single machine scheduling problem using approximate dynamic programming

Abstract: This paper addresses the non-preemptive single machine scheduling problem to minimize total tardiness. We are interested in the online version of this problem, where orders arrive at the system at random times. Jobs have to be scheduled without knowledge of what jobs will come afterwards. The processing times and the due dates become known when the order is placed. The order release date occurs only at the beginning of periodic intervals. A customized approximate dynamic programming method is introduced for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In the context of machine scheduling, Kanet and Sridharan (2000) showed that the schedules with inserted idle time are significant, especially in multimachine circumstances in which the earliness cost or dynamically arriving jobs come into play, and they also reveal that incorporating idle time is also beneficial for the machine scheduling problems with regular objectives, such as minimizing maximum lateness, flow time-related measures, and earliness/tardiness-related objective and maximum lateness. This observation is further validated in Ronconi and Powell (2010) that considered a single machine scheduling problem with artificial idle time to minimize total tardiness. In our IPDS model, since the orders are placed dynamically, and the objective is to minimize the waiting time, we consider inserting the idle times into production schedules.…”
Section: Literature Reviewmentioning
confidence: 60%
See 2 more Smart Citations
“…In the context of machine scheduling, Kanet and Sridharan (2000) showed that the schedules with inserted idle time are significant, especially in multimachine circumstances in which the earliness cost or dynamically arriving jobs come into play, and they also reveal that incorporating idle time is also beneficial for the machine scheduling problems with regular objectives, such as minimizing maximum lateness, flow time-related measures, and earliness/tardiness-related objective and maximum lateness. This observation is further validated in Ronconi and Powell (2010) that considered a single machine scheduling problem with artificial idle time to minimize total tardiness. In our IPDS model, since the orders are placed dynamically, and the objective is to minimize the waiting time, we consider inserting the idle times into production schedules.…”
Section: Literature Reviewmentioning
confidence: 60%
“…It has been widely used in many scheduling problems, such as crane scheduling (Yuan & Tang, 2017), healthcare scheduling (Nasrollahzadeh et al, 2018), and transportation scheduling with dynamic requests (Ulmer et al, 2019). Nevertheless, ADP is rarely seen in the stochastic machine scheduling literature, where one representative work is Ronconi and Powell (2010) that deployed ADP to minimize total tardiness in a single machine scheduling problem with dynamic order arrivals and due dates. For parallel machine scheduling, besides the assignment of orders to machines, we also need to determine the order processing sequence on each machine, which greatly enlarges the action (decision) space because the complexity of determining a sequence grows factorially.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In [17], the E/T problem is solved for the case when the machine fails and resumes operation in accordance with the given allocation. Minimization of the number of tardy jobs is considered in [18][19][20][21]. The most complete review of the available results can be found in [22].…”
Section: Investigation Using Scheduling Theory Methodsmentioning
confidence: 99%
“…Also, he proposed a heuristic solution to determine the optimal sequence of jobs in general mode where processing times have arbitrary distribution. Ronconi and Powell (2010) solved stochastic single-machine problem with the purpose of minimization of total tardiness via proposing the approximate dynamic programming method. Mokhtari and Salmasnia (2015) employed the combination of Monte Carlo simulation and differential evolution metaheuristic algorithm in order to analyze a parallel processor system and minimize the expected value of completion time.…”
Section: Single-machine Scheduling Problemmentioning
confidence: 99%